1960
DOI: 10.2134/agronj1960.00021962005200080013x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Irrigation Waters in the South Carolina Coastal Plain and Effects of Chlorides in Irrigation Water on the Quality of Flue‐Cured Tobacco1

Abstract: Synopsis The chloride content of these waters ranged from 4 to 55 ppm. The average increase in percent chlorine in the cured leaf was 0.009 for each pound of chlorine added by the irrigation water. The smoking quality of the tobacco was lowered when the irrigation water contained 225 ppm chloride ions but the commercial grade was not affected significantly by chloride in the water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In contrast, no significant difference in Maryland (Mulchi, 1982), Virginia (Collins and Hawks, 1993), and Burley (Fuqua et al, 1976) tobacco yield when different amounts of chloride were added to soil has been reported. Also, Peele et al (1960) found a nonsignificant yield response of flue-cured tobacco to chloride levels (5 to 225 mg L −1 ) in irrigation water. Karaivazoglou et al (2005) reported that the effect of chloride in irrigation water on total cured product yield of Virginia tobacco was dependent on the N fertilization form, with nitrate N restricting the detrimental effects of chloride in irrigation water up to 40 mg Cl L −1 .…”
Section: Plant Growth and Cured Leaf Yieldmentioning
confidence: 94%
“…In contrast, no significant difference in Maryland (Mulchi, 1982), Virginia (Collins and Hawks, 1993), and Burley (Fuqua et al, 1976) tobacco yield when different amounts of chloride were added to soil has been reported. Also, Peele et al (1960) found a nonsignificant yield response of flue-cured tobacco to chloride levels (5 to 225 mg L −1 ) in irrigation water. Karaivazoglou et al (2005) reported that the effect of chloride in irrigation water on total cured product yield of Virginia tobacco was dependent on the N fertilization form, with nitrate N restricting the detrimental effects of chloride in irrigation water up to 40 mg Cl L −1 .…”
Section: Plant Growth and Cured Leaf Yieldmentioning
confidence: 94%
“…In two growing environments, total N and alkaloid concentration was lowered as Cl − application rate increased from 8 to 112 kg ha −1 (Warren, 1990). Reducing sugar concentration was reported to increase with Cl − application by Peele, Webb, and Bullock (1960) and Sierra (1966). Warren (1990) confirmed this observation in lower-stalk tobacco sourced from one research environment.…”
Section: Core Ideasmentioning
confidence: 99%
“…Conversely, reducing sugar concentration increased when Cl − application increased from 0 to 34 kg ha −1 (Tables 3 and 9). Reducing sugars and Cl − application were positively correlated by Peele et al (1960) and are inversely related to total alkaloid concentration (Flower, 1999). In the current study, cured leaf Cl − and N concentrations were inversely related, a fact previously reported by Skogley and McCants (1963) and Mulchi (1982).…”
Section: Total Alkaloids and Reducing Sugar Concentrationmentioning
confidence: 99%
See 2 more Smart Citations